Analysis Of The Effect Of Social Assistance And Capital Expenditure On Poverty - Irawan, Farhah Fauziyah; Junaidi, Junaidi; Sultan, Sultan (Institut Teknologi dan Sains Mandala, 2024)
Abstract This study aims to determine the effect of social assistance spending and spending capital on poverty rates in districts/cities in South Sulawesi, which consists of 24 regencies, and takes samples from the last three years, namely 2018 – 2020. This research uses secondary data in the form of expenditure data. social assistance, capital spending and poverty rates. The data is taken from the government's official website, namely the Central Statistics Agency (BPS). For the purposes of analysis in this study, panel data were used from all regencies/cities in South Sulawesi Province. In processing the data that has been obtained, namely using the Eviws application. The method used in this study is the method of data analysis stationary test, correlation test and Granger causality test. The results of this study indicate that first, social assistance spending funds have no significant effect on poverty. Second, capital spending has no significant effect on poverty. Third, spending on social assistance and spending on capital do not mutually influence each other.